Statin Treatment as a Targeted Therapy for APC-Mutated Colorectal Cancer - Shailes, Hannah; Tse, Wai Yiu; Freitas, Marta O.; Silver, Andrew; Martin, Sarah A. (Frontiers in Oncology, 2022)
Background Mutations in the tumor suppressor gene Adenomatous Polyposis Coli (APC) are found in 80% of sporadic colorectal cancer (CRC) tumors and are also responsible for the inherited form of CRC, Familial adenomatous polyposis (FAP). Methods To identify novel therapeutic strategies for the treatment of APC mutated CRC, we generated a drug screening platform that incorporates a human cellular model of APC mutant CRC using CRISPR-cas9 gene editing and performed an FDA-approved drug screen targeting over 1000 compounds. Results We have identified the group of HMG-CoA Reductase (HMGCR) inhibitors known as statins, which cause a significantly greater loss in cell viability in the APC mutated cell lines and in in vivo APC mutated patient derived xenograft (PDX) models, compared to wild-type APC cells. Mechanistically, our data reveals this new synthetic lethal relationship is a consequence of decreased Wnt signalling and, ultimately, a reduction in the level of expression of the anti-apoptotic protein Survivin, upon statin treatment in the APC-mutant cells only. This mechanism acts via a Rac1 mediated control of beta-catenin. Conclusion Significantly, we have identified a novel synthetic lethal dependence between APC mutations and statin treatment, which could potentially be exploited for the treatment of APC mutated cancers.